The Effectiveness of Digital-Based Marketing Science Teaching Innovation - B.M.A.S. Anaconda Bangkara; Eka Hendrayani; Cahyani Pratisti; Rudianto; Hermiyetti (International Journal of Social Science and Business, 2023)
This research emerged in response to the challenge of improving students' academic success in marketing science. With the development of digital technology, digital-based teaching methods are considered as potential innovations to enrich the learning experience. The main objective of this study is to evaluate the effectiveness of digital-based teaching innovations. It includes understanding whether the use of digital tools and interactive methods enhances students' understanding of marketing science concepts and academic performance. This study is a case study that focuses on the implementation of digital-based teaching methods in a marketing science education environment. The research subjects involved students participating in digital-based marketing science classes at the Sultan Muhammad Syafiuddin Islamic Institute in Sambas. This research applies a combined approach between qualitative and quantitative through digital-based teaching using various digital tools such as multimedia presentations, interactive online platforms, and virtual simulations. The results of this case study show that digital-based marketing science teaching innovation has a positive impact. Students show high interest, active participation, increased understanding of concepts, and improved academic performance. Overall, this research supports the effectiveness of digital-based teaching in marketing science. The integration of digital tools and interactive methods can improve the quality of education and provide a more engaging learning environment for students.